Dynamic Changes of Mitochondrial Fusion and Fission in Brain Injury after Cardiac Arrest in Rats. (28th December 2017) - Li, Yi; Tang, Qingqin; Wang, Peng; Qin, Jiahong; Wu, Haidong; Lin, Jiali; Huang, Zitong
Abstract : Mitochondria change their morphology dynamically by continual fusion and fission processes to fulfill their function. However, little is known about the effect of cardiac arrest on mitochondrial dynamics. This study aimed to investigate time-dependent change of the mitochondrial dynamics after brain ischemic injury in rats of cardiac arrest. After resuscitation, obvious neuronal injury, reduced adenosine triphosphate (ATP) levels, excessive reactive oxygen species (ROS) generation, decreased mitochondrial membrane potential (MMP), and increased release of mitochondrial cytochrome c were observed at 12 h and 24 h after cardiac arrest. Moreover, we found that elongation of mitochondria was observed at 4 h after cardiac arrest, whereas fragmented mitochondria were significantly increased, along with concomitant increase in the fission proteins Drp1 and Fis1 and a reduction in the fusion proteins Mfn1 and Mfn2 at 12 h and 24 h after cardiac arrest. Taken together, these findings suggest that imbalance in mitochondrial dynamics probably contributes to brain injury after cardiac arrest.